Determinant of internal auditor’s intention to perform whistleblowing: a proposed model - Qomaruddin, Ardy; Hudayati, Ataina (Proceeding UII-ICABE, 2020)
So many years passed after SOX, fraud in corporation does not show a significant decrease, and only 7 percent of the cases were revealed through a whistleblowing system. BPR is an organization that have a significant weakness in fraud. This paper aims to formulate a research model related to the determination of the intention of internal auditors at BPR to take whistleblowing actions. The model proposed in this paper is derived from Theory of Planned Behavior and Social Cognitif Theory. Variables used in this model are attitude, social norm, perceived behavioural control, self efficacy, and outcome expectation. This research is expected to make a theoretical, scientific, insightful, and literary contribution related to the factors that influence the intention of an internal auditor at BPR to conduct whistleblowing in terms of the TPB and SCT model.